MEMAKNAI PENGALAMAN HIDUP ORANG DENGAN HIV/AIDS KDS FLORES PLUS SUPPORT: SEBUAH REFLEKSI TEOLOGIS-BIBLIS - Blasius Trinold Asa (Jurnal Ledalero, 2011)
There is increasing public attention about HIV/AIDS networks of concern. This option for and with HIV/AIDS survivors demonstrates human compassion but also expresses the struggle for life. And precisely here we find a unique, deep and challenging inspiration in the Bible. The story of the healing at the pool of Siloam/Bethzatha (John 5) is a cry for compassionate justice for those who suffer, including those surviving HIV/AIDS. This essay records a reading of John 5 by members of an HIV/AIDS survivor and mutual support group. They relate who Jesus is for them and how, in Jesus, they have regained their self respect and the will to live. Both their experience of pain and rejection by both the local church and their individual families, and their restored humanity accomplished by themselves through the healing touch of Jesus, challenges the rest of us to cast aside our ingrained prejudices and, together with these survivors, experience the liberating touch of Jesus in our lives too. The healing touch of Jesus can destroy any reluctance we might still have, based on the prejudiced values of the surrounding society. This “popular” reading of John 5 shows how Jesus opened up a circle of freedom and salvation and can be read alongside more academic exegetical accounts. Keywords: penderita, ODHA, perhatian, belas kasih, demi kehidupan, kairos, peduli.